Cáncer de pulmón microcítico: revisión - Guillén, Carmen; Molina, María José (Psicooncología, 2006)
Twenty percent of all lung cancers are of small cells (CPCP). More than half occur to people aged 60 and more. Due to its fast dissemination, most of them show symptoms when diagnosed (90%). These symptoms can be derived from its locoregional extension, metastases or can have a paraneoplastical origin. Anamnesis and thorough physical exploration are essential for the initial evaluation and adequate treatment. In addition to a blood analysis with determination of enzymes such as lactate dehydrogenase which helps in prognosis, thorax and abdominal computed tomography (CT), bone gammagraphy and cerebral CT or magnetic resonance imaging (MRI) allow optimum estadification. Although CPCP is chemo- and radio-sensitive, small progress has been achieved in the last years and its mortality rate is high. The objective of this paper is to revise all these aspects related to CPCP.